The dynamic interaction between road density and land uses in West Malaysian cities - Muhammad Hussein, Muhammad Zaly Shah; Awang, Mohd. Noor; Ho, Chin Siong; Che Puan, Othman; Mohd. Ali, Hishamuddin; Said, Mohd. Nor; Katmon, Norizam (2005)
Urban planning theories state that changes in land uses affect the provision of road infrastructure and vice versa. Invariably, this interaction between land uses and road infrastructure, represented by road density, is a dynamic one. Many studies abroad have attempted to quantify this dynamic interaction. Using a two-steps approach, an empirical model that describes the interaction between land uses and road density has been developed for selected West Malaysian cities. The two steps require that, first, a regression model is developed that functionally linked road density and land uses, and second, simulating land use developments to predict changes in road density. In this paper, the evidence for the interaction is shown for two West Malaysian Cities – Johor Bahru and Kuantan. The calibration of the interaction models for these two cities shows promising result. The main advantage of such interaction models is that the model provides transport planners a planning (and, budgeting) tool to plan for future provision of road infrastructure.